Diet and feeding habits of Saurida tumbil (Bloch, 1795) from northern Kerala, South-west coast of India - Manojkumar, P. P.; Pavithran, P. P. (Indian Journal of Fisheries, 2016)
Composition of the diet of greater lizardfish Saurida tumbil (Bloch, 1795), caught from northern Kerala, south-west coast of India was studied and described. The stomachs of 1981 specimens were collected between January, 2012 and June, 2014. Analysis of stomach contents based on index of relative importance (IRI) revealed that this species is exclusively piscivorous. Contrary to other benthic predators of the study area, it mainly feeds on pelagic and demersal fishes (IRI = 63.2), molluscs (IRI = 17.86), crustaceans (IRI = 18.33) and other miscellaneous items (IRI = 2.54). The diet ofÂ S. tumbil were found to be related to the seasonal availability of resources, occurrence of juveniles of certain species and on the migration of fishes from nearby places to the study area. Significant changes in prey items were observed between predator length groups, but a positive, significant relationship was recorded between prey size and predator size (p<0.05). Statistical analysis indicated a uniform representation of different diets in the stomach. Maximum similarity in diet between different food items was found in April and November.